Analysis of Indonesian Tax Revenue - Amalia Wijayanti; Firmansyah Firmansyah (AFEBI Economic and Finance Review, 2016)
This study analyzes the long-run and short-run effect of macroeconomic factors, such as real Gross Domestic Product (GDP), inflation rate, exchange rate and government spending on Indonesia’s tax revenue during 1976-2013, by utilizing the Error Correction Model (ECM). The finding of the study demontrates that in the long-run; the real GDP, exchange rate, and government spending affect Indonesia’s tax revenue, except the inflation rate. In short-run, Indonesia’s tax revenue statisically affected by government spending, while others variable do not influence Indonesia’s tax revenue. Error Correction Term (ECT) coefficient is 0.221, explains incompatibility tax revenue occur in long-run is corrected of 22 percent in one period.JEL Classification: E01, E20, H20Keywords: Error Correction Model, Macroeconomic, Tax revenue